Can Arts-Based Interventions Enhance Labor Market Outcomes among Youth? Evidence from a Randomized Trial in Rio de Janeiro - Carla Calero; Carlos Henrique Corseuil; Veronica Gonzales; Jochen Kluve; Yuri Suarez Dillon Soares (Institute for the Study of Labor (IZA), 2014)
This paper provides findings of a small-scale, innovative labor training program that uses expressive arts and theatre as a pedagogical tool. The corresponding life skills training component is combined with a technical component teaching vocational skills. To our knowledge, this is the first paper to rigorously evaluate the effectiveness of a training program constructed around expressive arts. Using a randomized assignment of favela youth into program and control groups, we look at the short-run treatment effects on a comprehensive set of outcomes including employment and earnings as well as measures of personality traits and risk behavior. We find positive short-run employment and earnings impacts five months after the program finalized; no impacts are found for shorter periods. These short-run impacts are economically very large, compared to those typically found in the literature: a 33.3 per cent increase in the probability of being employed, and a 23.6 per cent increase in earnings. We find no evidence of significant program impacts on other outcomes, including personality-related traits, providing evidence that these traits may not be malleable for young adults in the short-run. We argue that the estimated labor market impacts are due to a combination of both skills formation and signaling of higher quality workers to employers.
Keywords: J24; J68; I38; 330; labor market training; youths; randomized controlled trial; life skills